Redefining ‘Idolatry’: The Discursive Reconciliation of K-Pop Fandom and Muslim Identity on YouTube - Nur Afifah; Vahit Göktaş (Journal of Digital Religion and Contemporary Society, 2026)
This study examines how Muslim K-pop fans in Indonesia navigate their religious identity in the digital sphere through the YouTube channel LearningByFasting. Using Norman Fairclough’s Critical Discourse Analysis approach and Gary R. Bunt’s Cyber-Islamic Environments framework, this study explores the relationship between language, ideology, and power in da’wah content that combines Islamic values with Korean popular culture. The results reveal a hybridity of discourse, where Islamic terms, such as tauhid and syirik, interact with fandom jargon, including idol, healing, and inspiration. This phenomenon reflects a symbolic negotiation between piety, modernity, and cultural globalization. Audience responses reveal a pattern of moderate digital da’wah, with 29% expressing religious inspiration, 17% criticizing moral issues, and the rest displaying a balanced dialogical attitude. This study concludes that the digital space serves as an arena for creative and inclusive reconstruction of religious identity, while affirming the potential of digital media as an empathetic means of da’wah that strengthens moderate Islam in the global era.